RESEARCH OF CLOUD MICROSERVICES BASED ON ASP.NET CORE TECHNOLOGY - СКІДАН, В. В.; НІКОНОВ, О. Я.; ВОЛІВАЧ, А. П.; ПАВЛЕНКО, В. М. (Technologies and Engineering, 2024)
Goal. Research of cloud microservices based on ASP.NET Core technology and the use of the Model-View-ViewModel MVVM architectural pattern, evaluation of technical advantages. Methodology. Research of cloud microservices based on ASP.NET Core technology is carried out on the basis of methods and algorithms for the analysis of software systems with the aim of improving their quality, security and productivity. Results. As a result of the research of cloud microservices based on ASP.NET Core technology, the efficiency of using the MVVM architectural pattern was analyzed. The MVVM architectural pattern allows for the separation of a program's interface, basic presentation and business logic into three distinct classes: the View, which encapsulates the interface and interface logic; the ViewModel, which encapsulates presentation logic and state; the Model, which encapsulates the program's business logic and data. This pattern enables the creation of more scalable and maintainable applications and simplifies the process of testing, support, and application development. Best practices for developing and maintaining microservices in the cloud using ASP.NET Core are explored. On the basis of ASP.NET Core technology and the MVVM architectural pattern, the «Online Gallery» web application for working with photo content has been developed. Scientific novelty. The use of the MVVM architectural pattern for building cloud microservices and ASP.NET Core technology is proposed. The advantages of using ASP.NET Core in the context of cloud microservices are explored. Practical value. The research conducted and the results obtained allow us to assess the advantages of implementing ASP.NET Core for cloud microservices, which is important for software architects, developers, and IT companies in general. The obtained results enable informed decisions when designing cloud microservices based on ASP.NET Core technology, which allows you to build more efficient, scalable and secure software systems. The conducted research is the basis for future research and effective implementations in the ever-evolving world of cloud computing and microservices.